2020
DOI: 10.1002/cphc.202000392
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Formation of Methylgermylene (HGeCH3)

Abstract: The methylgermylene species (HGeCH3; X1A′) has been synthesized via the bimolecular gas phase reaction of ground state methylidyne radicals (CH) with germane (GeH4) under single collision conditions in crossed molecular beams experiments. Augmented by electronic structure calculations, this elementary reaction was found to proceed through barrierless insertion of the methylidyne radical in one of the four germanium‐hydrogen bonds on the doublet potential energy surface yielding the germylmethyl (CH2GeH3; X2A′)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The time‐of‐flight (TOF) spectra recorded at m/z=106–100 are indistinguishable after scaling; this indicates that these species originate from a single reaction channel, i. e. Si (28 amu)+GeH 4 (78 amu)→SiGeH 2 (104 amu)+H 2 (2 amu). In this context, it is important to note that the atomic hydrogen elimination channel leading to SiGeH 3 isomers is endoergic by at least 62 kJ mol −1 ; [51] this channel is therefore closed considering the experimental collision energy of 11.8±0.3 kJ mol −1 . The ion counts at m/z =100‐106 originate from the SiGeH 2 products with a different combination of silicon and germanium isotopes (Table S1); lower m/z=103–100 are generated via dissociative electron impact ionization of the m/z=104 ( 28 Si 74 GeH 2 ) parent product(s) along with their isotopically substituted counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time‐of‐flight (TOF) spectra recorded at m/z=106–100 are indistinguishable after scaling; this indicates that these species originate from a single reaction channel, i. e. Si (28 amu)+GeH 4 (78 amu)→SiGeH 2 (104 amu)+H 2 (2 amu). In this context, it is important to note that the atomic hydrogen elimination channel leading to SiGeH 3 isomers is endoergic by at least 62 kJ mol −1 ; [51] this channel is therefore closed considering the experimental collision energy of 11.8±0.3 kJ mol −1 . The ion counts at m/z =100‐106 originate from the SiGeH 2 products with a different combination of silicon and germanium isotopes (Table S1); lower m/z=103–100 are generated via dissociative electron impact ionization of the m/z=104 ( 28 Si 74 GeH 2 ) parent product(s) along with their isotopically substituted counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…The intersystem crossing is feasible here for a number of reasons: First, the MSX geometric structure is rather similar to the structure of the 3 i1 local minimum, the MSX energy is only 0.1 kJ mol À 1 higher than that of 3 i1 and thus, the crossing would occur in the close vicinity of the triplet isomer initially formed in the Si + GeH 4 reaction. Second, other fates of 3 i1 are not competitive; the atomic hydrogen elimination channel from 3 i1 leading to SiGeH 3 isomers is endoergic by at least 62 kJ mol À 1 [51] is closed at the experimental collision energy of 11.8 kJ mol À 1 , whereas the H 2 elimination from 3 i1 on the triplet surface features high barriers of at least 139 kJ mol À 1 . Moreover, the experimentally detected Si(μ-H 2 )Ge ( 1 A') + H 2 product can be formed only on the singlet PES, which corroborates the feasibility of the triplet-singlet intersystem crossing.…”
Section: Discussionmentioning
confidence: 99%
“…As well as our investigations [12–32] other kinetic studies have been undertaken by the group of King and Lawrance [33–35] in the gas phase and also by the group of Leigh [36] in the liquid phase, mainly of organogermylenes, GeR 2 (R=Me, Ph). A recent study by the group of Kaiser [37] has reported on the generation and gas phase behaviour of methylgermylene. These investigations show that GeH 2 and GeR 2 typically undergo bond insertion reactions into Ge−H, Si−H and O−H bonds, π‐type addition reactions across C=C and C≡C bonds and reaction with lone pair donor molecules such as ethers.…”
Section: Introductionmentioning
confidence: 99%
“…For the C 2 H 3 isomers, the planar vinyl radical (C 2 H 3 ; 1 ; X 2 A′) with a C s point group is the most stable isomer, with the methylmethylidyne radical (CH 3 C; 2 ; X 2 A″) less stable by 205 kJ mol –1 . However, for the heteronuclear systems, the sequence of stability is reversed with methylsilylidyne (SiCH 3 ; 3 ; X 2 A″), methylgermylidyne (GeCH 3 ; 7 ; X 2 A″), and silylgermylidyne (H 3 SiGe; 11 ; X 2 A″) representing global minima with their corresponding vinyl-type counterparts 4 , 8 , and 12 less stable by 42, 103, and 29 kJ mol –1 , respectively. The distinction can be explained by the increased overlap of the valence s and p orbitals of the carbon atom compared to silicon and germanium . As for Ge 2 H 3 , the global minima within the six Ge 2 H 3 isomers is a vinyl-type planar radical germylgermylidyne (H 2 GeGeH; 19 ; X 2 A″), with an unpaired electron that belongs to the π-type orbital perpendicular to the molecular plane. In analogy to the vinyl (C 2 H 3 ; 1 ; X 2 A′)–methylmethylidyne (CH 3 C; 2 ; X 2 A″) isomer pair, the germylgermylidyne (GeH 3 Ge; 20 ; X 2 A″) isomer is higher in energy than the vinyl-type counterpart 19 .…”
Section: Introductionmentioning
confidence: 99%